STRATEGI PENGELOLAAN EKOSISTEM MANGROVE DI DUSUN PALUH MERBAU DESA TANJUNG REJOKABUPATEN DELI SERDANG (Mangrove Ecosystem Management Strategy at Dusun Paluh Merbau Tanjung Rejo Village Deli Serdang District) - Olivia Lumban Gaol; Pindi Patana; Yoes Soemaryono (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
Dusun Paluh Merbau is one of 13 villages at Desa Tanjung Rejo Kabupaten Deli Serdang with covering area of 4.114 Ha. Rapid population growth directly caused a pressure on natural resources. The purpose of this research was to describe the causes of mangrove ecosystem damage and mangrove ecosystem management strategy at Dusun Paluh Merbau Desa Tanjung Rejo Kabupaten Deli Serdang. This research was held from April to Mei 2016. It used descriptive qualitative method and SWOT Analysis for sustainable mangrove ecosystem management strategy. Mangrove species found were Rhizophora apiculata, Bruguiera cylindra, Avicennia marina, and Lumnitzera racemosa. Activities at mangrove ecosystem caused some damages in Dusun Paluh Merbau such asdeveloping agriculture, aquaculture, settlement and it’s supported by weakness of law enforcement. SWOT analysis quadrant for mangrove ecosystem management at Dusun Paluh Merbau is in 3rd quadrant that means this village has opportunity butit hasthe internal weakness too, so that difficult to achieve profitable opportunity. Turn Arround Quadrant brings in the W-O strategy as the priority alternative strategy for mangrove ecosystem sustainable management; socializing or awareness to the community about the importance of integrated sustainable natural resources management (W1, W2, W3, W4, O1, O2, O3, O4) gained the highest score 3,11.Keywords : Dusun Paluh Merbau, Management Strategy, Mangrove, SWOT Analysis.